Regional income inequality in rural China, 1985 - 2002: Trends, causes and policy implications - Guanghua Wan (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2007)
This paper depicts the trend of regional inequality in rural China for the period 1985-2002. The total inequality is decomposed into the so-called within- and between-components when China is divided into three regional belts (east, central and west). A regression-based accounting framework is then used to explore root sources of the rising inequality. Policy implications are discussed.
Keywords: O18; P2; D63; 330; China; inequality; spatial decomposition; rural; Ländliches Einkommen; Regionale Einkommensverteilung; China